2019
DOI: 10.1016/j.idairyj.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation, and application of a fast, simple, and robust SPE-based LC-MS/MS method for quantification of angiotensin I-converting enzyme inhibiting tripeptides Val-Pro-Pro, Ile-Pro-Pro, and Leu-Pro-Pro in yoghurt and other fermented dairy products

Abstract: Dairy products are an important part of a nutritionally balanced diet as their constituents can affect the human state of health. By inhibiting the angiotensin I-converting enzyme, the tripeptides Val-Pro-Pro, Ile-Pro-Pro, and Leu-Pro-Pro can lower blood pressure. As these peptides are produced during fermentation, they are found in various dairy products like cheese, yoghurt, etc., but except for cheese only little is known about their content. To investigate how other dairy products contribute to a supply of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although IPP, VPP, and LPP have been proved clinically effective in reducing the blood pressure of antihypertensive patients and several functional foods have been developed based on them, IPP and VPP are often designated as the major bioactive agents and LPP is often not detected or detected at a low level. A survey of 49 dietary products revealed that LPP was present only in few curds and was not found in the selected sour cream, crème fraiche, sour milk, or yoghurt products 41 ; Evolus® milk, however, which is the first product sold in Europe with a scientifically established claim to control blood pressure, contains only 0.8 mg L −1 LPP, which is much lower than the 6.9 mg L −1 of VPP and 6.1 mg L −1 of IPP 42 . Hence the current hydrolysate might be used as a novel antihypertensive ingredient, with LPP as the major bioactive ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…Although IPP, VPP, and LPP have been proved clinically effective in reducing the blood pressure of antihypertensive patients and several functional foods have been developed based on them, IPP and VPP are often designated as the major bioactive agents and LPP is often not detected or detected at a low level. A survey of 49 dietary products revealed that LPP was present only in few curds and was not found in the selected sour cream, crème fraiche, sour milk, or yoghurt products 41 ; Evolus® milk, however, which is the first product sold in Europe with a scientifically established claim to control blood pressure, contains only 0.8 mg L −1 LPP, which is much lower than the 6.9 mg L −1 of VPP and 6.1 mg L −1 of IPP 42 . Hence the current hydrolysate might be used as a novel antihypertensive ingredient, with LPP as the major bioactive ingredient.…”
Section: Resultsmentioning
confidence: 99%